1973
DOI: 10.1021/jo00942a018
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small ring heterocyclic compounds. XLII. 1,3-Dipolar cycloaddition reactions of the azomethine ylide derived from the 1,3-diazabicyclo[3.1.0]hex-3-ene system

Abstract: 4, hex-3-ene reacts stereospecifically with dimethyl maléate and dimethyl fumarate in refluxing xylene or on irradiation to give A2-pyrrolines as cycloadducts. The base-catalyzed epimerization of the various adducts supports the stereochemical structure assignments. A likely mechanism for these additions is the conversion of the diazabicyclo system into an azomethine ylide, which subsequently reacts with the unsaturated substrate. The photochemical results imply that the opening of the aziridine ring proceeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…61 The thermal or photochemical cleavage of aziridines is a well known source of azomethine ylides that undergo 1,3-dipolar cycloaddition reactions. [62][63][64] Tsuge and coworkers found that 4-isoxazolines can be used as precursors of azomethine ylides in 1,3-dipolar cycloaddition reactions and exemplified this via intramolecular addition to a pendant furan ring. 56 The reaction of N-methylnitrone 41a with dimethyl acetylenedicarboxylate…”
Section: Methodsmentioning
confidence: 99%
“…61 The thermal or photochemical cleavage of aziridines is a well known source of azomethine ylides that undergo 1,3-dipolar cycloaddition reactions. [62][63][64] Tsuge and coworkers found that 4-isoxazolines can be used as precursors of azomethine ylides in 1,3-dipolar cycloaddition reactions and exemplified this via intramolecular addition to a pendant furan ring. 56 The reaction of N-methylnitrone 41a with dimethyl acetylenedicarboxylate…”
Section: Methodsmentioning
confidence: 99%
“…11: mp 1 19-120°( lit. 119°,56 120-121 °);59 ir (CHC13) 2600-3400 (CQ2H), 1680 (C=0), 1630 (C=C); nmr (CDC13) 11.22 (broad s, 1 H, C02H), 6.95 (m, 1 H, C=CH), 2.60 (t, J = 6.8 Hz with further splitting, 4 H, CH2C=C), 2.20 (distorted quintet, J = 6.8 Hz, 2 H, CH2C/y2CH2); mass spectrum m/e (%) 40 (30), 41 (97), 43 (26), 44 (24), 55 (29), 65 (34), 66 (60), 67 (100), 69 (28), 94 (25), 112 (86), 1 13 (6).…”
Section: R = Ch" Phmentioning
confidence: 99%
“…12: mp 89-90°; ir (CC14) 1775, 1710 (CO-O-CO), 1625 (C=C); nmr (CC14) 6.95 (broad s, 1 H, C=CH), 2.55 (m, 4 H, CH2C=C), 2.10 (m, 2 H, CH2C//2CH2); uv (95% ethanol) 220 (< 10,000); mass spectrum m/e (%) 41 (34), 67 (43), 95 (100), 178 (7); 206 (-0.01); exact mass (caled for Cl2H1403, 206.09429) 206.09367 ± 0.00338.…”
Section: R = Ch" Phmentioning
confidence: 99%
See 2 more Smart Citations